Malaria of return : an anthropology of malaria risk among migrant travelers from sub-Saharan Africa in Bordeaux - (:unkn) unknown (My University, 2018)
France is the industrialized country most assigned by import malaria with around 4735 imported and registered cases in 2016. Migrant travelers from malaria-affected countries residing in France account for 82.2% of all malaria cases. malaria infections. This thesis mainly seeks to analyze the issue of the use of malaria risk prevention among migrant travelers from sub-Saharan African countries in Bordeaux. Based on direct observations and individual interviews with different actors, this research shows the heterogeneity of situations of exposure to malaria risk during temporary return to the country of origin. This risk depends on the experiential and socio-economic situations, as well as the burdens it is supposed to assume. When these burdens are significant, the migrant traveler tends to prioritize the risks, with a non-prioritization of malaria control in favor of the risk of “toubabisation”, socially less accepted. The non-prioritization of the risk of malaria is accentuated by a banal, ordinary and daily perception of malaria in the context of migration and by the non-reimbursement of chemoprophylaxis by the National Health Insurance Fund. This work shows that the non-use of chemoprophylaxis is influenced by the lack of experience of malaria in France and severe malaria in the country of origin. Often, the experience of this disease must be experienced and perceived in the host country to induce a change of perception and therefore a future use of prevention. Therapeutically, this thesis highlights delayed diagnosis of malaria in general practice. These delays are caused by the lack of association of the “return fever” and symptoms associated with malaria, and by its “exoticism” in France. As such, this research contributes to reflections in the fields of anthropology of health and anthropology of travel risk, with the example of migrant travelers exposed to malaria risk.
Keywords: African Research